Polyhydroxyalkanoates Production from Ralstonia Pickettii Bacteria: Structural and Mechanical Studies - Asranudin Asranudin; Surya Rosa Putra; Adi Setyo Purnomo; Dalia Allouss; Holilah Holilah; Lisman Suryanegara; Alvin Romadhoni Putra Hidayat; Alvin Rahmad Widiyanto; Muchammad Tamyiz (Green Engineering Society, 2022)
Bacterial Polyhydroxyalkanoates (PHAs) are a remarkably versatile category of biodegradable polymers with a variety of applications in the packaging, agricultural, biomedical, and pharmaceutical fields. In the present study, bacterial PHAs films are characterized by Fourier transform infrared (FTIR), Scanning electron microscope (SEM), Gas chromatography-mass spectroscopy (GC-MS), Differential scanning calorimetry (DSC), and Universal testing machine (UTM). It was found that almost 20% (w/w) of PHAs was produced from Ralstonia pickettii, and the five major types of the produced polymer were validated via FTIR analysis, i.e., 1046-1185 cm-1 (C-O stretching), 1723 cm-1 (C=O stretching), 2974-2926 cm-1 (CH3 and CH2 stretching) and 3450 cm-1 (OH stretching). The GC-MS chromatogram generated two main peaks, i.e., 2-butenoic acid methyl ester and 4-hexenoic acid methyl ester, at retention times of 4.62 min and 5.79 min, respectively. The main compounds of 2-butenoic acid methyl ester and 4-hexenoic acid methyl ester had percentage areas of 28% and 43%, respectively. Based GCMS analysis shows two monomer PHAs ie. 2-butenoic acid methyl ester and 4-hexenoic acid methyl ester, correspondingly. The blending of PHAs R. pickettii and PEG-400 positively decreases thermal properties and tensile strength and increases elongation at break.